(3TQM GdCSeGA GdMSfis - (3eLghds
(3ChdgG (B:s
(3bGd Gddg JYGdi (B: ( (3hddg GdCSeGA GdMSfi aGOYhg HgG s
(3BNQgG (B:s
(3ef cGf Hg eQV Ch eTbI Ch eUjHI Ch hLY ai LSOg jbQC gPG GdGSe KdGKI hKdGKjf eQI aEfg jHQC HEPf Gddg JeJ GdCSeGA GdMSfi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HQSe eMeO Hf YHO Gddg Hf GdgGOis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs